(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This dissertation is devoted to the analysis and improvement of mechanisms for assessing and minimizing risks in the process of investment management, with a specific focus on the industrial sector. The research is based on the case study of Akfa Aluminum, one of Uzbekistan’s leading industrial enterprises.